2017
DOI: 10.1111/jfpp.13402
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory effect of acid concentration, aging, and different packaging onEscherichia coliO157:H7 and on color stability of beef

Abstract: The presence of pathogens such as Escherichia coli O157:H7 (EC) represents risks to public health and to economy of Brazilian beef industry. In this context, the application of lactic acid (LA) is an efficient practice employed to reduce bacterial count without compromising consumer safety. Our aim was to verify the inhibitory effect of LA application combined with aging and different packaging on EC and its effects on beef color. The LA effect on EC counts was concentration dependent during aging and storage,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 48 publications
(65 reference statements)
0
9
0
Order By: Relevance
“…Previous studies also reported pH increases in sardines stored under refrigeration (Chaijan et al, ; Pinheiro et al, ). Considering the comparison between treatments, it is well known that acidic conditions reduce the microbial load of foods (Salim et al, ). However, acidic conditions also cause protein denaturation, which leads to the formation of alkaline amino acids and increase in pH (Rawdkuen, Jaimakreu, & Benjakul, ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies also reported pH increases in sardines stored under refrigeration (Chaijan et al, ; Pinheiro et al, ). Considering the comparison between treatments, it is well known that acidic conditions reduce the microbial load of foods (Salim et al, ). However, acidic conditions also cause protein denaturation, which leads to the formation of alkaline amino acids and increase in pH (Rawdkuen, Jaimakreu, & Benjakul, ).…”
Section: Resultsmentioning
confidence: 99%
“…The differences among treatments can be explained by the acceleration of myoglobin denaturation and heme pigment oxidation caused by acidic medium (Pipek, Sikulova, Jelenikova, & Izumimoto, 2005), resulting in early meat browning (Salim et al, 2018). Synthetic and natural antioxidants inhibit the production of free radicals or scavenge them, preventing meat discoloration (Augustyniak et al, 2010;Kaewprachu et al, 2017).…”
Section: Color Stabilitymentioning
confidence: 99%
“…Organic acids are regarded as an alternative compound for microbiology control in the food industry due to their secure handling, low cost, and quick action [ 43 ]. Lactic acid had a linear inactivation pattern in both strains.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, the direct use of organic acids in the processing of beef is allowed by the European Union and the United States of America to decrease the total count of microorganisms [ 44 , 54 ]. However, the use of organic acids is not permitted in Brazil for beef production [ 43 ]. The use of organic acid in the animal production system in Brazil is only approved for chicken processing during the sanitization step and the acetic acid as a growth promoter.…”
Section: Discussionmentioning
confidence: 99%
“…Beef products, mainly ground beef, are considered ideal substrates for spoilage and pathogenic bacteria growth, resulting in a rapid loss of quality and limited shelf life [2]. This fact, together with an increased demand for the use of nonthermal processing technologies as an alternative for preserving the meat's original quality, makes it necessary to find new technological approaches for ground beef preservation [3,4]. Brazilian beef cuts are commonly displayed in vacuum packages in retail displays [1].…”
Section: Introductionmentioning
confidence: 99%